College Writing Skills - Underwood, Virginia and Kett, Merriellyn (Columbus Charles E. Merrill Publishing Company, 1981)
College Writing Skills, Second Edition, is designed so that it may be used by a whole class or assigned individually by chapter to students with particular problems. We have tried to provide sufficient grammatical information within each chapter to accomplish the goals of the chapter. Extensive grammatical terminology may prove an unnecessary hurdle for many students. However, if more help in identifying subjects and verbs is needed, Appendix A provides additional sentences that may be used with or without the explanatory text.
Keywords: Writing